Rough sets and knowledge technology : 10th International Conference, RSKT 2015 : held as part of the International Joint Conference on Rough Sets, IJCRS 2015, Tianjin, China, November 20-23, 2015 : proceedings /: 10th International Conference, RSKT 2015 : held as part of the International Joint Conference on Rough Sets, IJCRS 2015, Tianjin, China, November 20-23, 2015 : proceedings. (2015) - Unknown
No abstract available